Prevalence of anaemia among females of the reproductive age group visiting Chisapani dispensary - Bhatia, V.; Manandhar, N.; Mishra, B.; Bista, S.; Shah, M. (Journal of Institute of Medicine Nepal, 1999)
Anaemia is one of the major health problems in Nepal. Nutritional anaemia is oneof the commonest forms of anaemia and affects chiefly the females in the reproductiveage group. The available data from the hospital records and small-scale studies putthe estimate to more than 50%. There are other figures that project the range from 60-75% among this group. The present study was conducted on females of thereproductive age group visiting the dispensary attached to Nepalgunj Medical College,Chisapani. The total number of females included in the study was 71. Nearly 65% wereless than 30 years of age. The literacy rate was around 39.4%. Among the 66 marriedfemales, the number of children ranged from 0-7. Among the subjects, 79% were foundto be anaemic. The proportion of female with anaemia was not associated withincreasing age or education of the subjects but some degree of association could beobserved with increasing number of children. Usage of temporary contraceptive wasalso found to be associated with a larger proportion of females being anaemic. Thedegree of contribution made by hookworm infestation to the present figures of anaemiacannot be commented upon in numerical terms but could be high.